Правові особливості договірного оформлення трудових відносин у сільськогосподарському переробному кооперативі - Гайдаржи, X. А.; Гайдаржи, К. А.; Gajdarzhi, Kh. A. (Одеса : Юрид. л-ра, 2012)
The issues of conclusion of the labor agreements in the agricultural reprocessing cooperative have been described. The classification of the workers of the agricultural reprocessing cooperative have been given. The approaches to improving the treaty formulation of labor relations in the agricultural reprocessing cooperative have been provided.
Гайдаржи X. А. Правові особливості договірного оформлення трудових відносин у сільськогосподарському переробному кооперативі / Х. А. Гайдаржи // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 412-417.
Keywords: сільськогосподарський переробний кооператив; трудовий договір; контракт; статут; сельскохозяйственный перерабатывающий кооператив; трудовой договор; контракт; устав; agricultural reprocessing cooperative; labor agreement; contract; statute